Identification of causes and mitigation measures of construction fall accidents of class a and class b contractors in Shah Alam area / Normadiana Mohammad Hanapi … [et al.] - Mohammad Hanapi, Normadiana; Mohd Kamal, Mohd Mawardi; Ismail, Muhammad Isha; Putera Abdullah, Indra Akmal (2013)
The construction industry is one of the most hazardous industries. It is because those who spend their working lives on construction sites have a higher probability of being killed at workplace. Based on the statistics issued by the Social Security Organization (SOCSO) Malaysia, the number of fatality and permanent disablement cases due to fall accidents at the construction sites is one of the highest rates as compared to other sector. Therefore, this research is intends to identify the cause and safety measure of construction fall accidents in Shah Alam construction sites because there are a lot of high rise buildings project in this state. This study is carried out by doing literature review and getting feedback through questionnaires. In order to find out cause and mitigation measure of fall accident at the construction site, this study used SPSS test such as Spearman's Rho to analyze the data. The finding of this study indicates that "poor safety altitude and behavior of workers" are the main problems in obstructing the implementation of safety procedures and guidelines for construction sites. The responses from the survey also show that "sufficient safety training" and "equipments for working at height" are the adoptable mitigation measure to enhance the workers' safety performance. It is believed that appointing the competent person in inspection and maintenance works and by applying risk assessment in identifying fall hazards could reduce the number of fall accidents.